Analyzing The Impact Of Media Relation Strategy, Internal Organizational Relations, And Reward And Punishment Strategy On Company Performance - Yasmina Diani Hanafiah; Visda Fitri Wahidah; Vallery Imanuel (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to investigate the impact of media relations strategy, internal organizational relations, and reward & punishment strategy on company performance. Employing a qualitative approach, the research utilizes in-depth interviews and document analysis as primary data collection techniques. A purposive sampling method is employed to select participants from various organizational levels within the target companies. Data analysis involves thematic coding and constant comparison to identify patterns and relationships among the variables. Preliminary findings suggest that an integrated approach to media relations, fostering positive internal organizational relationships, and implementing balanced reward & punishment systems positively influence company performance. The study contributes to the understanding of how strategic communication and organizational dynamics intersect to shape organizational outcomes.